3D Physical Experimental Study of Shield–Strata Interaction Under Dynamic and Static Disturbance - Yang, Shengli; Yue, Hao; Zhai, Ruihao; Cui, Zhiwei; Wei, Xia (Frontiers in Earth Science, 2022)
With the increasing depth as well as intensity of coal mining, there is an increasing risk to the working face due to high static load and periodic breakage of the roof. The relation between the support and the surrounding rock under static-dynamic coupling loading disturbance is an important factor affecting the stability of the working face. In this paper, a 3D physical modelling platform is developed to study interaction between the shield and strata under dynamic and static disturbance. In the experiment, the static load is set to 0, 0.5, 1 and 2 MPa respectively. The different dynamic load is realized by changing the fall height of the iron plate. The change of hydraulic support resistance is recorded by the pressure monitoring system. The displacement of the coal wall is monitored by infrared rangefinder. The results show that the change of static load and dynamic load will affect the support resistance and coal wall displacement. With the increase of dynamic load, coal wall displacement and bracket resistance increase, the increase is not linear. The larger the dynamic load, the greater the increase. Static load change has little effect on bracket resistance, the impact on coal wall displacement is large. With the increase of static load, coal wall displacement is reduced and then increased. Static load for the stability of coal wall there is a threshold, below the threshold, static load can improve the stability of coal wall, exceed the threshold but accelerate the destruction of coal wall. At the same time, the stability coefficient of quarry bracket and surrounding rock is defined. The sensitivity analysis of the main parameters is carried out. The method of controlling the stability of quarry bracket and surrounding rock is proposed.